Integrasi Teknologi Digital dan Program Penghijauan di LKSA untuk Meningkatkan Kesadaran Lingkungan - Mesran, Mesran; Suginam, Suginam (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
This article discusses the integration of digital technology with greening programs at Child Welfare Institutions (LKSA) as an effort to increase environmental awareness. By utilizing advances in digital technology, this program aims to provide effective and interesting education to children about the importance of preserving the environment. This program involves the use of educational applications, social media, and other digital platforms to convey information about the environment, farming techniques, and ways to keep the surrounding environment clean and beautiful. Apart from that, this program also involves practical activities such as planting trees and creating green parks around LKSA. In its implementation, digital technology is used to facilitate communication and coordination between LKSA managers, volunteers and other related parties. This makes it easier to monitor and evaluate the program, so that necessary adjustments can be made to achieve optimal results. The use of technology also enables the dissemination of information and program results widely via the internet, so that it can inspire and motivate other institutions to do the same. The results of implementing this program show a significant increase in LKSA children's knowledge and awareness of environmental issues. They become more concerned about the surrounding environment and are actively involved in greening activities. Apart from that, this program also contributes to improving air quality and the beauty of the environment around LKSA. The integration of digital technology in the greening program at LKSA has proven effective in increasing children's environmental awareness. This program not only provides in-depth education, but also teaches practical skills that are useful for their future. Thus, this integration model is suitable for application in other institutions to support sustainable environmental conservation efforts